Heart's Ease: Eudaimonia, Musicking in the Pandemic, and Its Implications for Music Education - Boyce-Tillman, June (Frontiers in Psychology, 2021)
This article will review the themes found in the literature on eudaimonia: • Ethical behaviour • A sense of meaning and purpose • Autonomy – being able to make wise decisions and manage behaviour • Contemplation • Relationship with spirits of the ancestors and celestial beings • Relationships of mutuality, respect It will use these to critique various events online during the pandemic, such as the Embodiment conference, the SHIFT conference and the ZOOM peace choir. These developments related to music and wellbeing will be used to interrogate the purposes of music education and what might be learned from these new developments in relation to technology in relation to themes, such as values, orality and literacy, process and product